A control strategy for improved efficiency in direct-coupled photovoltaic systems through load management. (1st December 2018) - Azzolini, Joseph A.; Tao, Meng
Highlights: A generic control strategy based on load management is proposed and demonstrated. The efficiency approaches 100% without a conventional maximum power point tracker. The voltage variation can be reduced to less than ±3% without a DC/DC converter. The system can be backed by the electric grid to eliminate its intermittency. Application of the control strategy for electric vehicle charging is presented. Abstract: Nearly all photovoltaic (PV) systems involve power management and/or conversion devices. Each of these devices introduces a power loss and has an associated monetary cost. In this paper, a direct-coupled load-managing PV system is proposed that promises both a lower cost and a higher efficiency than conventional systems. Against the prevailing wisdom that the PV power must be managed, the proposed system varies the power demand of the loads by controlling the number of loads connected to the PV array to extract the maximum available power throughout a day without a conventional maximum power point tracker. This system can also regulate its operating voltage to less than ±3% of its target voltage without a DC/DC converter. The proposed control strategy can be applied to many direct-coupled PV systems for improved efficiency. A simulation program was developed for the load-managing system that can simulate its performance with a PV array of any size and any number of loads. The theoretical system efficiency was found to increase with the number of loads being managed and reaches above 99% for a direct-coupled system with just eight ohmic loads. Experimentally, a prototype system with equal and unequal ohmic loads was demonstrated in an outdoor environment that responds to changes in solar irradiance. The control strategy also allows direct-coupled PV systems to be backed up by a secondary power source, e.g. the electric grid, to eliminate their intermittency for applications such as electric vehicle charging. The cost of the control electronics for the load-managing system is less than 1% of the commercial-scale PV system cost. Several challenges in implementing and optimizing the proposed system are discussed.